The Quasi-Contract in the English Law. A Comparative Study with the Unjustly Paid in the Iraqi Civil Law - علي يونس صلاح الدين (Journal of Legal Sciences, 2021)
Quasi-contract is considered as one of the well-established legal systems of the English Common law of customary origins, which is unwritten and based upon judicial precedents of the English courts. It is worth-bearing in mind that the legal basis of quasi-contract passed into two different stages: in the first stage the English judicature, supported by some juristic opinions regarded it as an implied Contract made by courts to prevent one party from being unjustly enriched at the expense of the other. Whereas in the second stage the English judicature considered it as an independent source of obligation، based upon the law of restitution. and having nothing to do with the law of contract. The Iraqi civil law No. (40) of 1951 regulated the unjust enrichment and considered it as an independent source of obligation also, with the unjust payment being its main application.